Small steps - Sachar, Louis 1954- (New York Delacorte Press, 2006)
Three years after being released from Camp Green Lake, Armpit is trying hard to keep his life on track, but when his old pal X-Ray shows up with a tempting plan to make some easy money scalping concert tickets, Armpit reluctantly goes along
1
Keywords: African Americans -- Fiction; Cerebral palsy -- Fiction; Interpersonal relations -- Fiction; Juvenile delinquents -- Rehabilitation -- Fiction; People with disabilities -- Fiction; Singers -- Fiction